2003
DOI: 10.1002/hlca.200390009
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Crystal Structure Analysis of Oxindole Alkaloids

Abstract: The single-crystal X-ray structures of speciophylline, mitraphylline, and rhynchophylline, oxindole alkaloids from the Peruvian climbing vine Uncaria tomentosa (Rubiaceae), were determined. The three compounds show N ¥¥¥ HÀN hydrogen bonding, which has not been observed in the crystal structures of the related alkaloids pteropodine and isopteropodine. In the tetracyclic alkaloid rhynchophylline, the side chain is rotated out of the ring plane into a position perpendicular to it. This is in contrast to the situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…From the aqueous methanolic extract of the stem bark of M. africanus collected in Nigeria, seven Corynanthetype oxindole alkaloids, i.e., rhynchophylline, 7) isorhynchophylline, 7) corynoxeine, 8) isocorynoxeine, 8) ciliaphylline, 8) rhynchociline, 8) and isospecionoxeine, 8) were isolated. In addition, three lignans, i.e., (ϩ)-dihydrodehydrodiconiferyl alcohol, 9) (ϩ)-isolariciresinol, 10) and (ϩ)-isolariciresinol-3a-O-b-D-glucopyranoside, 11) two secoiridoids, i.e., sweroside 12) and dihydroepinaucledal 2 13) (first example as natural product), scopoletin, and quinovic acid 3b-O-b-6-deoxy-D-glucopyranosyl-28-b-D-glucopyranosyl ester 14) were obtained.…”
mentioning
confidence: 99%
“…From the aqueous methanolic extract of the stem bark of M. africanus collected in Nigeria, seven Corynanthetype oxindole alkaloids, i.e., rhynchophylline, 7) isorhynchophylline, 7) corynoxeine, 8) isocorynoxeine, 8) ciliaphylline, 8) rhynchociline, 8) and isospecionoxeine, 8) were isolated. In addition, three lignans, i.e., (ϩ)-dihydrodehydrodiconiferyl alcohol, 9) (ϩ)-isolariciresinol, 10) and (ϩ)-isolariciresinol-3a-O-b-D-glucopyranoside, 11) two secoiridoids, i.e., sweroside 12) and dihydroepinaucledal 2 13) (first example as natural product), scopoletin, and quinovic acid 3b-O-b-6-deoxy-D-glucopyranosyl-28-b-D-glucopyranosyl ester 14) were obtained.…”
mentioning
confidence: 99%
“…From the methanol (MeOH) extract of the leaves of Mitragyna hirsuta collected in Thailand one new heteroyohimbine-type oxindole alkaloid, isomitraphyllinol (1), was isolated, together with four heteroyohimbinetype oxindole alkaloids, i.e., mitraphylline (2) [12,13], isomitraphylline (3) [12], isomitraphylline N-oxide (4) [14], and isopteropodine (5) [12], and one Corynanthetype oxindole alkaloid, rhynchophylline (6) [13,15] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…(8). Comparison of those spectra with those of known alkaloids, rhynchophylline (6) with C7(R) [25] and isorhynchophylline (8) with C7(S), indicated that the spiro center of 31 and 32 had the S configuration. The C3 stereochemistry was elucidated by NOE experiments.…”
Section: -2 Alkaloids In Uncaria Attenuatamentioning
confidence: 92%